Pindi Balochan: Exhibiting pathway of climate resilience - Singh, Rajbir; Kumar, Rakesh; Singh, S. Vanider Deep; Nayak, A. K. (Indian Farming, 2025)
In India, green revolution has brought food security through improved varieties and technologies, however, overexploitation has led to soil pollution, environmental degradation, high use of synthetic fertilizers, etc. Pindi Balochan, is one of those villages in Punjab facing these challenges besides climatic variability. To address these challenges, interventions of KVK, Faridkot under National Innovations on Climate Resilient Agriculture (NIRCA) has helped in adoption of climate resilient agriculture through crop residue management, agroforestry, and improved livestock practices. The story of Pindi Balochan reaffirmed that with the right integration of technologies, innovations, traditional knowledge, empowered communities, and supportive policies, even the most vulnerable rural landscapes could transition towards resilient livelihoods, sustainable ecosystems, and long-term climate stewardship.